(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Set expressions are an important part of stylistics as they represent fixed or semi-fixed combinations of words with specific meanings and stylistic functions. They contribute to the expressiveness, emotional colouring, and cultural richness of language. This article examines the role of idioms, proverbs, clichés, collocations, and phraseological units in stylistic analysis and highlights their functions in different types of discourse.